2008
DOI: 10.1074/jbc.m710422200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Major Liver Lysophosphatidylcholine Acyltransferase

Abstract: Phosphatidylcholine (PC) is synthesized through the Kennedy pathway, but more than 50% of PC is remodeled through the Lands cycle, i.e. the deacylation and reacylation of PC to attain the final and proper fatty acids within PC. The reacylation step is catalyzed by lysophosphatidylcholine acyltransferase (LPCAT), and we report here the identification of a novel LPCAT, which we named LPCAT3. LPCAT3 belongs to the membrane-bound O-acyltransferase (MBOAT) family and encodes a protein of 487 amino acids with a calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
174
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(199 citation statements)
references
References 30 publications
13
174
2
Order By: Relevance
“…In mouse, LPCAT2 (53) and LPCAT3 (49) have been suggested to show a preference for AA. In human cells, it is LPCAT3 the form that appears to exhibit preference for AA, although also by linoleic acid (50,52). Shindou et al (53) have recently reported the increase of lyso-platelet-activating factor acetyltransferase activity in RAW364.7 cells transfected with the mouse lyso-platelet-activating factor acetyl transferase/LPCAT2 gene and stimulated with TLR agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse, LPCAT2 (53) and LPCAT3 (49) have been suggested to show a preference for AA. In human cells, it is LPCAT3 the form that appears to exhibit preference for AA, although also by linoleic acid (50,52). Shindou et al (53) have recently reported the increase of lyso-platelet-activating factor acetyltransferase activity in RAW364.7 cells transfected with the mouse lyso-platelet-activating factor acetyl transferase/LPCAT2 gene and stimulated with TLR agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Four isoforms of LPCAT exist in mammalian cells, termed LPCAT1, LPCAT2, LPCAT3, and LPCAT4 (45-51), but only two of them, LPCAT2 and LPCAT3, have been documented to participate in AA reacylation reactions (49)(50)(51)(52)(53). Human peripheral blood monocytes express both LPCAT2 and LPCAT3 (data not shown).…”
Section: Lpcat3 Regulates Pl Aa Incorporation In Activated Cellsmentioning
confidence: 99%
“…With the cloning of Lpcat family members in recent years, it has become clear that these enzymes are responsible for PC remodeling and the generation of polyunsaturated PCs in various tissues. Lpcat3 is the major Lpcat isoform in the small intestine and liver (6). It has been shown that ablation of Lpcat3 in the small intestine at early stages of life is neonatally lethal and diminishes the incorporation of arachidonic acid into PCs within the cell membrane, leading to the impaired triglyceride mobilization and lipoprotein production (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments employ an established, immortal and metabolically active human hepatocellular carcinoma cell line, Huh7, used extensively in studies of hepatocyte metabolism [13][14][15] . Since facilitated uptake of glucose and fructose by the transmembrane GLUT2 transporter is demonstrated in Huh7 cells [16] , these cells provide an excellent model for studies of carbohydrate-induced lipogenesis. Accordingly, the studies herein were carried out to determine whether hepatocyte lipogenesis, in an in vitro cell culture model, is modulated by adjusting culture media monosaccharide content and concentration.…”
Section: Introductionmentioning
confidence: 99%